2017
DOI: 10.5194/angeo-35-751-2017
|View full text |Cite
|
Sign up to set email alerts
|

Modelling geomagnetically induced currents in midlatitude Central Europe using a thin-sheet approach

Abstract: Abstract. Geomagnetically induced currents (GICs) in power systems, which can lead to transformer damage over the short and the long term, are a result of space weather events and geomagnetic variations. For a long time, only high-latitude areas were considered to be at risk from these currents, but recent studies show that considerable GICs also appear in midlatitude and equatorial countries. In this paper, we present initial results from a GIC model using a thinsheet approach with detailed surface and subsur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 39 publications
0
61
1
Order By: Relevance
“…BP17 then showed how this method could be used to demonstrate the influence of the geomagnetic coast effect on power networks using a hypothetical square network as well as for the test case network of Horton et al (2012). More recently, Richardson and Beggan (2017) confirmed that the LP85 method used to model GIC in the United Kingdom, Ireland, Austria, and New Zealand (Bailey et al, 2017;Beggan et al, 2013;Blake et al, 2016;Divett et al, 2017) correctly calculates the transformer-level current of the test case in Horton et al (2012). It is this implementation of LP85, which we extend in the present study.…”
Section: 1029/2018sw001814mentioning
confidence: 98%
See 1 more Smart Citation
“…BP17 then showed how this method could be used to demonstrate the influence of the geomagnetic coast effect on power networks using a hypothetical square network as well as for the test case network of Horton et al (2012). More recently, Richardson and Beggan (2017) confirmed that the LP85 method used to model GIC in the United Kingdom, Ireland, Austria, and New Zealand (Bailey et al, 2017;Beggan et al, 2013;Blake et al, 2016;Divett et al, 2017) correctly calculates the transformer-level current of the test case in Horton et al (2012). It is this implementation of LP85, which we extend in the present study.…”
Section: 1029/2018sw001814mentioning
confidence: 98%
“…Modeling GIC is useful to understand the impact of geomagnetic storms on power systems. A standard approach to modeling GIC, used, for example, by Koen and Gaunt (2003), Torta et al (2012), Beggan et al (2013), Blake et al (2016), Bailey et al (2017), and Divett et al (2017), has been to use the method of Lehtinen and Pirjola (1985;LP85 hereafter). In these applications of the LP85 method substations are approximated as a single resistance to Earth and it is usually assumed that equal levels of GIC flow through each transformer in a substation.…”
Section: Introductionmentioning
confidence: 99%
“…Computations of the GEF within the second, most populated, group of papers (Beggan et al, ; Bailey et al, , ; Divett et al, ; Dimmock et al, ; Liu et al, ; Marshall et al, ; Nakamura et al, ; Püthe & Kuvshinov, ; Püthe et al, ; Pokhrel et al, ; Rosenqvist & Hall, ; Wang et al, , among others) rely on a numerical modeling of the GEF, either with a thin sheet or fully 3‐D conductivity models of the Earth. 3‐D conductivity models can be compiled using, for instance, results of regional MT surveys or/and exploiting global and regional maps of bathymetry, sediment thickness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A quasi 3‐D approach that has been employed in a number of GIC studies is the thin sheet conductivity model (Vasseur & Weidelt, ), whereby conductivity gradients such as the ocean‐continent boundaries are included by employing a thin sheet conductance map overlying layered resistivity structures. This method has been used in GIC studies of power systems in the UK (Beamish et al, ; Beggan et al, ; Kelly et al, ; Thomson et al, ), France (Kelly et al, ), Austria (Bailey et al, , ), and New Zealand (Divett et al, , ). The thin‐sheet model is a period‐dependent model that requires satisfaction of a range of conditions, as discussed by Weaver (), and is physically viable for periods in a certain range.…”
Section: Introductionmentioning
confidence: 99%